Cryogenic high-pressure torsion of a single-phase CoCrFeNiMn high-entropy alloy: Nanoindentation strain-rate sensitivity and creep deformation behavior - M. Zare Ghomsheh; F. Khodabakhshi; G. Khatibi; B. Weiss; C. Rentenberger; E. Schafler (Materials & Design)
The localized mechanical behavior of a high entropy alloy (HEA) by analyzing its deformation mechanisms under different indentation loading levels and loading rates assessed. The CoCrFeNiMn HEA was prepared using arc melting and casting methods and then exposed to severe plastic deformation (SPD) applying the high-pressure torsion (HPT) technology. This SPD modification resulted in the refinement of the grain size of the HEA to ultra-fine and nano-scale sizes, along with the generation of structural defects that look like twins and stacking faults. The impact of varying grain size after HPT at room (300 K) and cryogenic temperatures (77 K) on the rate-sensitive depth-sensing mechanical and time-dependent plastic deformation (creep) behaviors was assessed using single- and multiple-cycles of nanoindentation loading. The results showed that the primary, HPT 300 K, and HPT 77 K alloys exhibited strain-rate sensitivity (SRS) values of around 0.011, 0.031, and 0.027, respectively, by nanoindentation testing, paired with relatively small activation volumes of 55b3, 7b3, and 10b3. These calculated trends of SRS value and variations of creep deformation depth for the examined materials were discussed in correlation with the characterized microstructural aspects in the form of sub-grains and dislocation’s structure, which were analyzed using advanced microscopy techniques.